Clinical phenotype associations with various types of anti-dsDNA antibodies in patients with recent onset of rheumatic symptoms. Results from a multicentre observational study. Issue 1 (3rd April 2014) - Compagno, Michele; Rekvig, Ole P; Bengtsson, Anders A; Sturfelt, Gunnar; Heegaard, Niels H H; Jönsen, Andreas; Jacobsen, Rasmus Sleimann; Eilertsen, Gro Ø; Fenton, Christopher G; Truedsson, Lennart; Nossent, Johannes C; Jacobsen, Søren
Abstract : Despite anti-dsDNA antibodies constitute a wide range of specificities, they are considered as the hallmark for systemic lupus erythematosus (SLE). Objective: To identify clinical phenotypes associated with anti-dsDNA antibodies, independently of any clinical diagnoses. Methods: Patients with recent onset of any rheumatic symptoms were screened for antinuclear antibodies (ANA). All ANA-positive and matching ANA-negative patients were examined, and their clinical phenotypes were registered, using a systematic chart formulated after consensus between the participating centres. All patients were tested for different anti-dsDNA antibody specificities with assays habitually used in each participating laboratory. Crithidia Luciliae Immuno Fluorescence Test (CLIFT) was performed three times (with two different commercial kits); solid and solution phase ELISA were performed four times. Associations between clinical phenotypes and results of anti-dsDNA assays were evaluated by linear regression analysis (LRA) and principal component analysis (PCA). Results: Totally, 292 ANA-positive and 292 matching ANA-negative patients were included in the study. A full dataset for statistical analysis was obtained in 547 patients. Anti-dsDNA antibodies were most frequently detected by ELISA. LRA showed that overall positivity of anti-dsDNA antibodies was associated with proteinuria and pleuritis. Alopecia was significantly associated only with CLIFT-positivity. Besides confirming the same findings, PCA showed that combined positivity of CLIFT and ELISA was also associated with lymphopenia. Conclusions: Our results show that different anti-dsDNA antibody specificities are associated with nephropathy, pleuritis, alopecia and lymphopenia, regardless of the diagnosis. It may challenge the importance of anti-dsDNA antibodies as a diagnostic hallmark for SLE.